What University Teachers Consider Important in Teaching Subject Didactics to Future Primary School Teachers - Krass, Tiia; Uibu, Krista; Sikkal, Esta (International Electronic Journal of Elementary Education, 2025)
Teacher’s competence has a great impact on development of knowledge and cognition in the society. In order to teach effectively, university teachers need to know the content and structure of the subject they teach, knowledge of subject didactics and principles of general pedagogy. The aim of the study was to investigate how the university teachers perceive their competence in teaching subject didactics across its domains of knowledge, their attitudes and teaching skills. Data was collected by interviewing 11 university teachers instructing Estonia’s future primary school teachers and analysed by thematic analysis. The results revealed that subject content, teaching methods and goals as well as requirements of curriculum and educational legislation are important aspects for building up subject didactics courses. The university teachers aimed at developing students’ core competencies for delivering lessons. According to university teachers, teaching skills, creative teaching, different learning styles and formats in subject didactics courses were seen as tools for building an inspiring learning environment. The need for more systematic and coherent cooperation of teachers of subject didactics within the university and other educational institutions was highlighted. It will facilitate the advancement of teachers’ professional knowledge to enhance primary school teachers’ instruction.